GENDER DEFINITION OF MUSICAL ART IN THE EDUCATIONAL SYSTEM - V. V. Poliuha (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The article interprets the gender issues and their interconnection of musical art that leads to analyzis of music pedagogy and educational system in general. The purpose of the study is the selection and analysis of such gender definitions of music as ender dimension, gender roles, gender approach, the gender component in the system of music education. Methodology of the study is based on the interdisciplinary approach that involves the use of scientific methods of analysis, synthesis and synthesis. Also, there is the method of comparative analysis and analogy applied in understanding the problems related to the study of gender influence in art and education. Originality is reflected in modern educational concept that appeals to the understanding of gender issues as a way of more thorough understanding of individuals, their role status of the individual, which in turn defines social opportunities in educational activities. Accordingly, the modern science can not remain uninvolved into the problems of modern times. Conclusions. Studies of gender in musical art education leads to selection, analyzis and understanding of such definitions as: gender dimension, which is focused on the understanding of the principle of obtaining polysynthetic, gender sensation from a musical work; gender roles, which distinguish representation of women in different kinds of music; gender approach, which establishes the availability of gender imbalance in the system of music education; gender component, which distinguishes the importance of understanding and practical implementation of gender equality in the system of music education.